2008
DOI: 10.1007/s10750-008-9669-5
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the meiofauna paradox: dispersal and colonization of nematodes and other meiofaunal organisms in low- and high-energy environments

Abstract: How do small, benthic meiofaunal organisms become cosmopolitan over large geographic ranges? Abiotic forces including oceanic currents are believed to be of key importance in aiding marine meiofaunal dispersal. We investigated the effect of distance from substrate and site exposure on meiofaunal colonization and transport in the water column. First, we tested how distance from substrate and sediment grain size affected colonization of azoic sediments by meiofauna in a sheltered inlet. Nematodes, crustacean nau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 44 publications
1
55
1
Order By: Relevance
“…This may be attributed to the tidal current of 9 cm/s, able to resuspend and transport the most abundant genera which dwell in the uppermost sediment layers in muddy areas (COMMITO & TITA 2002). Although nematodes are considered poor swimmers (PALMER 1984, FEGLEY 1985, they are commonly found in plankton samples (BOECKNER et al 2009) and at the sediment-water interface. However, their abundance in the water column is always much lower than in the sediment (PALMER 1984).…”
Section: T Longicaudatamentioning
confidence: 99%
See 2 more Smart Citations
“…This may be attributed to the tidal current of 9 cm/s, able to resuspend and transport the most abundant genera which dwell in the uppermost sediment layers in muddy areas (COMMITO & TITA 2002). Although nematodes are considered poor swimmers (PALMER 1984, FEGLEY 1985, they are commonly found in plankton samples (BOECKNER et al 2009) and at the sediment-water interface. However, their abundance in the water column is always much lower than in the sediment (PALMER 1984).…”
Section: T Longicaudatamentioning
confidence: 99%
“…The rapid dispersal of meiofauna has been ascribed primarily to water column processes, including passive erosion and active emergence, which exert a major influence on recruitment and colonisation in larger spatial scales (CHANDLER & FLEEGER 1993, COMMITO & TITA 2002. Passive largescale dispersal modes may include transportation through the water column, erosion/suspension, emersion/suspension and rafting on algal mats and floating debris (BOECKNER et al 2009, DERYCKE et al 2008.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…If conspecific, the ubiquity of this species along the Atlantic Ocean to support the "meiofauna paradox", in which small benthic organisms with little mobility and without planktonic larval stages can be dispersed over large geographic ranges (Giere, 1993). It was experimentally demonstrated that even weak currents are able to suspend and transport meiofaunal organisms and moreover these are capable of active dispersal into the water column (BOECKNER et al, 2009). In this way, further studies also are necessary in order to investigate possible patterns of population structuration along the species distributional ranges.…”
Section: Resultsmentioning
confidence: 99%
“…Since our data support the hypothesis of an amphi-oceanic distribution of D. dievengatensis, this strengthened the paradox. Such long distance dispersal may be human mediated, through ballast water for example (Radziejewska et al, 2006), or may be related to current-driven sediment transport (Boeckner et al, 2009).…”
Section: Molecular Analysesmentioning
confidence: 99%